2004
DOI: 10.1177/039463200401700208
|View full text |Cite
|
Sign up to set email alerts
|

Integrin β2-Chain (CD18) Over-Expression on CD4+ T Cells and Monocytes after Ischemia/Reperfusion in Patients Undergoing Primary Percutaneous Revascularization

Abstract: beta2-integrin subunit (CD18) plays an essential role in leukocyte recruitment and adhesion in sites of endothelial injury. We analyzed the surface expression of CD18 on T lymphocytes and monocytes in a series of patients presenting acute coronary syndrome (ACS) who underwent primary percutaneous intervention (PCI) for coronary artery revascularization. We found that basal CD18 expression on peripheral blood-derived CD4+ (but not CD8+) T lymphocytes was significantly increased in ACS patients as compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
2
13
0
1
Order By: Relevance
“…This means that sorting into MVBs can determine both the delivery of transmembrane proteins to lysosomes and the extracellular space, and also the ability of endocytosed receptors to transmit signals. Finally, in accordance with recent perspectives (36)(37)(38)(39)(40) showing the importance of endocytic processes in regulating the activity and distribution of receptormediate signals we demonstrated that CD38 cell surface signalling is down-regulated by endocytosis but, persisting at MVBs level, might have a positive role in the intracellular signalling.…”
Section: Discussionsupporting
confidence: 91%
“…This means that sorting into MVBs can determine both the delivery of transmembrane proteins to lysosomes and the extracellular space, and also the ability of endocytosed receptors to transmit signals. Finally, in accordance with recent perspectives (36)(37)(38)(39)(40) showing the importance of endocytic processes in regulating the activity and distribution of receptormediate signals we demonstrated that CD38 cell surface signalling is down-regulated by endocytosis but, persisting at MVBs level, might have a positive role in the intracellular signalling.…”
Section: Discussionsupporting
confidence: 91%
“…Myocardial necrosis, www.cardiologyjournal.org which can range from a minor elevation of cardiac enzymes to a large infarct, is the most common complication following PCI. Microembolization of plague debris during PCI procedure has been proposed as the most likely cause of myocardial necrosis [18], and myocardial necrosis could also be associated with ischemia and reperfusion injury after stent implantation and sudden blood supply of ischemic myocardial tissues [19]. Cardiac troponins are a more sensitive marker than CK-MB in detecting minor degrees of myocardial necrosis following PCI [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of chemokines by mimosine can henceforth affect the outcome of the inflammatory response (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), the products of which are also important for initiating tissue repair, by chemoattracting immune cells into a wound site. Our study contributes to a better understanding of the mechanism by which blood cells profoundly affect inflammatory responses in vivo and suggests that the inhibitor ofMCP-1 and MIP-2, L-mimosine, may have its effects on inflammatory conditions produced by parasites.…”
Section: Discussionmentioning
confidence: 99%